Chemical Composition and Antimicrobial Activity of Selected Essential Oils against Staphylococcus spp. Isolated from Human Semen - Miroslava Kačániová; Margarita Terentjeva; Jana Štefániková; Jana Žiarovská; Tatsiana Savitskaya; Dmitrij Grinshpan; Przemysław Łukasz Kowalczewski; Nenad Vukovic; Eva Tvrdá (MDPI AG, 2020)
Staphylococcus spp. is not only a commensal bacteria but also a major human pathogen that causes a wide range of clinical infections. Recent evidence suggests that Staphylococcus has the ability to colonize the reproductive system and to affect its structure and functions. The objective of this study was to determine the chemical properties and antibacterial effects of select essential oils (EOs): Amyris balsamifera L., Boswellia carterii Birdw., Canarium luzonicum (Blume) A. Gray, Cinnamomum camphora (L.) J. Presl., Cinnamomum camphora var. linaloolifera Y. Fuita, Citrus x aurantium L., Gaultheria procumbens L., Litsea cubeba (Lour.) Pers., Melaleuca ericifolia Smith., Melaleuca leucadendra L., Pogostemon cablin (Blanco) Benth., Citrus limon (L.) Osbeck, Santalum album L., and Vetiveria zizanoides (L.) Roberty against 50 Staphylococcus spp. cultures isolated from human semen, specifically Staphylococcus aureus, S. capiti, S. epidermidis, S. haemoliticus, and S. hominis. The disc diffusion and broth microdilution methods were used to assess the antimicrobial potential and to determine the minimum inhibitory concentration (MIC) of the selected EOs. The best anti-Staphylococcus activities were found with both methods for the essential oils of C. luzonicum (Blume) A. Gray, A. balsamifera, C. camphora, and P. cabli.